2007
DOI: 10.1073/pnas.0611107104
|View full text |Cite
|
Sign up to set email alerts
|

Spatial determinants of poverty in rural Kenya

Abstract: This article investigates the link between poverty incidence and geographical conditions within rural locations in Kenya. Evidence from poverty maps for Kenya and other developing countries suggests that poverty and income distribution are not homogenous. We use spatial regression techniques to explore the effects of geographic factors on poverty. Slope, soil type, distance/travel time to public resources, elevation, type of land use, and demographic variables prove to be significant in explaining spatial patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 7 publications
7
82
1
6
Order By: Relevance
“…Adaptation (and coping) strategies do not automatically reduce household poverty, just like poverty reduction activities do not automatically improve capacity to respond to climatic stresses (Eriksen and O'Brien 2007). There are complex dynamics that exist in determining levels of poverty (see for example Okwi et al 2007;Krishna et al 2006). The literature provides valuable arguments concerning the need to consider both the direct impact of other stressors, and how coping with one stress can indirectly shape (2005) found, households prone to drought may relocate closer to water sources to cope with reduced water availability, yet in doing so increase their exposure and vulnerability to unexpected short term shocks such as flooding.…”
Section: Coping With Climate Induced Hazards In Rural Households In Umentioning
confidence: 99%
“…Adaptation (and coping) strategies do not automatically reduce household poverty, just like poverty reduction activities do not automatically improve capacity to respond to climatic stresses (Eriksen and O'Brien 2007). There are complex dynamics that exist in determining levels of poverty (see for example Okwi et al 2007;Krishna et al 2006). The literature provides valuable arguments concerning the need to consider both the direct impact of other stressors, and how coping with one stress can indirectly shape (2005) found, households prone to drought may relocate closer to water sources to cope with reduced water availability, yet in doing so increase their exposure and vulnerability to unexpected short term shocks such as flooding.…”
Section: Coping With Climate Induced Hazards In Rural Households In Umentioning
confidence: 99%
“…Auer argues that good governance is the key to sustainable development, comparing Equatorial Guinea with Botswana, whose GDP grew an average of 7% between 1995 and 2005. Okwi et al (2007) analyzed geographic determinants of poverty with regression models including slope, soil type, distance/travel time to public resources, elevation, type of land use, and demographic variables. Their results indicated that investments in roads and improvements in soil fertility potentially reduce poverty rates.…”
Section: Economic Developmentmentioning
confidence: 99%
“…The pastoral livelihood zone, made up by northern and northeastern Kenya (Wajir, Marsabit and Tana River districts), experienced the highest net poverty increase (27%) over the 15-year period, while the high potential livelihood zone and the urban districts experienced marginal poverty reductions (1% each). Okwi et al (2007) explored the links between GIS-based environmental data and spatial poverty differences across Kenya. They found evidence of geographic poverty traps and that different spatial determinants of poverty (e.g.…”
Section: Differences Across Livelihood Zonesmentioning
confidence: 99%